Emotional Support and Family Strategies for Patients with Chronic Kidney Disease Undergoing Hemodialysis - Kristian, Eben Haezar; Andri, Florensius; Hermawan, Stepanus Maman (CV. Global Health Science Group, 2025)
Chronic Kidney Disease (CKD) is a progressive medical condition that imposes significant physical, psychological, and social burdens on both patients and their families. Long-term hemodialysis therapy demands substantial involvement from family members, not only in logistical support but also in providing emotional stability. However, the emotional role and adaptive strategies of families in supporting CKD patients remain underexplored, particularly in the context of long-term care. This study aims to explore the emotional roles and coping strategies employed by family caregivers of CKD patients undergoing hemodialysis. A qualitative approach with an interpretative phenomenological design was applied. Twelve participants, all immediate family members of patients receiving regular hemodialysis at Hospital X in Pontianak, Indonesia, were selected through purposive sampling. Data were collected through semi-structured in-depth interviews and analyzed using Interpretative Phenomenological Analysis (IPA). The trustworthiness of the data was enhanced through triangulation and member checking. The study identified four major themes: (1) The Emotional Role of the Family in Accompanying the Patient; (2) Adaptive Strategies for Families in Facing the Challenges of Mentoring; (3) Psychosocial Challenges in the Mentoring Process; and (4) Family Meanings and Expectations in Assisting CKD Patients. Family caregiving was found to be not only burdensome but also an opportunity for emotional growth and personal transformation. This study highlights the need for structured psychosocial support and counseling services for families, and proposes the development of a comprehensive family-centered caregiving model in hemodialysis units.